Rethinking school discipline in the Caribbean: the move away from corporal punishment - Morris-Francis, Sherill (The Palgrave handbook of Caribbean criminology, 2024)
The idea of rethinking school discipline in the Caribbean culture must include a critical scrutiny of the concept from an African-Caribbean historical perspective. Historically, corporal punishment has received widespread support throughout the Caribbean. It is imperative to consider that traditional child-rearing practices by colonial enslavers included corporal punishment as an integral part of ensuring discipline and control. However, despite all independent English Speaking Caribbean countries being signatories to the Convention on the Rights of the Child and Articles 19 and 28 of the Convention which oblige all parties to prohibit and eliminate all types of violence against minors and that schools must practice disciplinary measures that conform to the Convention, corporal punishment is still an acceptable form of discipline. This chapter presents a brief overview of the history and theoretical perspective of school discipline in the Caribbean, a review of the status of school discipline, and a reflection on strategies implemented as the Caribbean moves from corporal punishment to establishing positive school climates that achieve conformity through persuasion and other non-violent disciplinary measures.